Analisis Partisipasi Anggota Kelompok Tani Hutan Pada Kegiatan KTH Di Kota Padang - Mekar Sari Eka Putri; Hery Bachrizal Tanjung; Zul Irfan (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2023)
Management Forestry Social conducted by Group farmer Forest (KTH) in shape activity KTH covers manage institutional, manage area, and manage effort. In reach purpose activity KTH this needed participation from member KTH. In Padang city area there is 2 (two) location Forestry Social with scheme Forest societal ( HKm ), however participation member second KTH this still low. For that, need study deep for answer how participation member KTH on activity KTH at KTH Sikayan Balumuik, KTH Padang Janiah, and Padang City, as well as factors what which influence participation. Study this is study explanatory ( survey ) and quantitative. Next in analysis data used regression linear double which processed use application IBM SPSS Statistics 20. Level participation member KTH on activity KTH Sikayan Balumuik in category tall. Factor which affect it is level education formal, role companion as advocate, and Support market. Level participation member KTH on activity KTH Padang Janiah in category low. Factor which affect it is Support government, and Support market. Next for level participation member KTH on activity KTH in Padang City in category tall which influenced by level education formal Support government, Support stake holders other, and Support market